2021
DOI: 10.1038/s41598-021-84092-1
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Stay-at-home policy is a case of exception fallacy: an internet-based ecological study

Abstract: A recent mathematical model has suggested that staying at home did not play a dominant role in reducing COVID-19 transmission. The second wave of cases in Europe, in regions that were considered as COVID-19 controlled, may raise some concerns. Our objective was to assess the association between staying at home (%) and the reduction/increase in the number of deaths due to COVID-19 in several regions in the world. In this ecological study, data from www.google.com/covid19/mobility/, ourworldindata.org and covid.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 54 publications
1
24
0
1
Order By: Relevance
“…Unlike some authors, our data showed that most social relaxing events had a limited effect on SARS-CoV-2 cases [1][2][3]9]. However, our study is in line with a large ecological study that reported a drop in cases of COVID-19 even after two months of opening bars, restaurants and pubs [6]. It is possible that the population continued to adhere to the protection measures against infection, in addition to restrictions imposed on opening hours, number of regulars and distancing between groups.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Unlike some authors, our data showed that most social relaxing events had a limited effect on SARS-CoV-2 cases [1][2][3]9]. However, our study is in line with a large ecological study that reported a drop in cases of COVID-19 even after two months of opening bars, restaurants and pubs [6]. It is possible that the population continued to adhere to the protection measures against infection, in addition to restrictions imposed on opening hours, number of regulars and distancing between groups.…”
Section: Discussionsupporting
confidence: 85%
“…This study based in primary data reinforce model studies that indicate that reopening events have different effects on the COVID-19 series, although the type of event is still a matter of debate. It is possible that the attitude of residents towards the pandemic, through continued wearing of masks, taking personal precautions, testing for COVID-19 and keeping social distancing, added to the adhesion of commercial establishments is the key factor to reduce risk of transmission in public places [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Precautions at home to avoid spreading the virus include the following: self-isolation including staying at home 4,[63][64][65][66][67][68][69][70][71][72] ; avoiding touching other people [73][74][75][76][77] ; staying isolated in a specific room away from other people 4,11,[78][79][80] ; use of a separate bathroom or washroom if possible [80][81][82][83][84][85][86][87] ; avoidance of sharing personal household items with other people or pets where possible and if not possible, these items should be cleaned with soap and warm water 88,89 ; avoid handling pets 90,91 ; and wearing a mask covering the nose and mouth when around other poeple. 16,19,20,81,[92][93][94] Cleaning and disinfection are recommended on a daily basis including all high-touch surfaces, [95][96][97][98] the practice of meticulous washroom hygiene, and any surfaces that may be contaminated with blood, 95 stool, 83 or body fluids.…”
Section: Resultsmentioning
confidence: 99%
“…We have therefore performed these calculations for all dichotomous series (lockdown, curfew), and it is interesting to note that we obtained the coefficients as those directly obtained with Pearson. This method has previously been used to study the relationship between COVID-19 mortality and containment 16 .…”
Section: Methodsmentioning
confidence: 99%